Correlation between neutrophil percentage-to-albumin ratio and all-cause and cerebrovascular mortality among hypertension patients - You Li; Cheng Yu (Scientific Reports)
Abstract Neutrophil percentage-to-albumin ratio (NPAR) is a novel inflammatory biomarker and correlated with the progression and clinical outcomes of many diseases. This investigation aimed to clarified the association between NPAR and mortality risk among hypertension patients. The database of the National Health and Nutrition Examination Survey provided the patient data for hypertension. Using a restricted cubic spline (RCS), the association between the NPAR and mortality risk was investigated. In order to assess the independent risk contribution of the NPAR in all-cause and cerebrovascular mortality, weighted Cox proportional hazards models were employed. Concordance index and receiver operating characteristic (ROC) curve were employed to assess how effectively the NPAR predicted the mortality risk at different times. A total of 6,866 hypertension cases was included in this investigation. During follow-up, 2,757 (40%) patients have died, 582 (8.5%) of them from cerebrovascular disease. RCS regression analysis found a positive nonlinear correlation between NPAR and all-cause and cerebrovascular mortality of hypertension patients. High NPAR indicated higher risks of all-cause mortality (HR = 1.81, 95% CI 1.52–2.37) and cerebrovascular mortality (HR = 2.21, 95% CI 1.67–2.88) among hypertension patients, and these results remained after adjusting certain clinical parameters. The areas under the curve of for 5-year, 10-year and 15-year ROC for all-cause mortality were 0.720, 0.703 and 0.634, and those for cerebrovascular mortality were 0.705, 0.706 and 0.699, respectively. NPAR served as s a biomarker for all-cause and cerebrovascular mortality in hypertension patients. Higher NPAR indicated higher risk of all-cause and cerebrovascular mortality.